Determinants and prognostic significance of exercise pulmonary hypertension in asymptomatic severe aortic stenosis - Lancellotti, Patrizio; Magne, Julien; Donal, Erwan; O'Connor, Kim; Dulgheru, Raluca; Rosca, Monica; Pierard, Luc A (Circulation (New York, N.Y.), 2012)
Recent studies emphasized the usefulness of exercise stress echocardiography in asymptomatic patients with aortic stenosis. Nevertheless, the additive value of exercise pulmonary hypertension (Ex-PHT) in such patients remains unexplored. We therefore aimed to identify the determinants and to test the impact on outcome of Ex-PHT in asymptomatic patients with severe aortic stenosis. Asymptomatic patients with severe aortic stenosis (n=105; aortic valve area <0.6 cm(2)/m(2); age, 71±9 years; male, 59%) and preserved left ventricular systolic function (ejection fraction ≥55%) were prospectively submitted to exercise stress echocardiography. Resting PHT and Ex-PHT were defined as a systolic pulmonary arterial pressure >50 and >60 mm Hg, respectively. Ex-PHT was more frequent than resting PHT (55% versus 6%; P<0.0001). On multivariable logistic regression, the independent predictors of Ex-PHT were male sex (odds ratio, 4.3; P=0.002), resting systolic pulmonary arterial pressure (odds ratio, 1.16; P=0.002), exercise indexed left ventricular end-diastolic volume (odds ratio, 1.04; P=0.026), exercise e'-wave velocity (odds ratio, 1.35; P=0.047), and exercise-induced changes in indexed left atrial area (odds ratio, 1.36; P=0.006). Ex-PHT was associated with reduced cardiac event-free survival (at 3 years, 22±7% versus 55±9%; P=0.014). In a multivariable Cox proportional hazards model, Ex-PHT was identified as an independent predictor of cardiac events (hazard ratio, 1.8; 95% confidence interval, 1.0-3.3; P=0.047). When exercise-induced changes in mean aortic pressure gradient were added to the multivariable model, Ex-PHT remained independently associated with reduced cardiac event-free survival (hazard ratio, 2.0; 95% confidence interval, 1.1-3.6; P=0.025). In asymptomatic patients with severe aortic stenosis, the main determinants of Ex-PHT are male sex, resting systolic pulmonary arterial pressure, and exercise parameters of diastolic burden. Moreover, Ex-PHT is associated with a 2-fold increased risk of cardiac events. These results strongly support the use of exercise stress echocardiography in asymptomatic aortic stenosis.